Adverse trends of cardiovascular risk factors among low risk populations (1983-1994) - a cohort study of workers and farmers in Guangzhou, China - Liu Xiaoqing; Mai Jinzhuang; Rao Xuxu; Zhuo Qiling; Guo Chengye; Gao Xiangmin; Wu Yong; Deng Mulan; Lin Shuguang (BMC, 2011)
Abstract Background The levels and trends of cardiovascular risk factors vary greatly throughout China. We examine 10-year trends of cardiovascular risk factors (1983-1994) and the factors related to these trends among low-risk cohorts of workers and farmers in Guangzhou, China. Methods This is a cohort study of 3,131 workers and 3,493 farmers aged 25-64 years at baseline with 10 years of follow-up. We performed a longitudinal analysis to account for the aging of the cohorts and the repeated measures of the same individual. Results At baseline the prevalence of overweight (including obese) ranged from 1.0% to 11.8%, hypertension ranged from 3.8% to 10.5%, and mean serum total cholesterol (TC) ranged from 155.4 mg/dl to 187.2 mg/dl. Although prevalence of smoking declined, blood pressure levels and body mass index (BMI) increased significantly, and lipid profiles changed unfavorably during the 10-year follow-ups. The prevalence of hypertension increased from 5.0 percentage points (female farmers) to 12.3 percentage points (male farmers). Mean TC increased significantly (e.g., +22.8 mg/dl and +17.0 mg/dl in male and female farmers, respectively). In the longitudinal data analyses, increase in BMI was associated with increase in blood pressure levels and TC. Significant adverse trends of risk factors persisted after adjustment for aging, education, BMI, smoking, and alcohol intake. Conclusion Urgent action is needed to prevent and reverse the unhealthy trends occurring among these low risk Chinese workers and farmers.